House Privacy in Densely Populated Settlements - Pribadi, Septana Bagus; Lestari, Ria Ripardi Wahyu; Hidayat, Fahmi Syarif; Farah, Khalda Nur (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
The phenomenon of houses without road access has been happening a lot lately, especially in densely populated settlements. This happens because neighbors block access or are unwilling to provide a road. In contrast to this phenomenon, one of the residents in the densely populated settlement of Leuwigajah Village, Cimahi City allowed part of his land to be used as a road for his neighbors who have houses without access. However, this condition has an impact on territory, privacy and the hijab in the residence. The aim of this research is to examine the application of a house privacy in a densely populated settlement. The research method used is qualitative with a descriptive analytical approach. Primary data was obtained through field observations and interviews, while secondary data was obtained from literature studies. Data is collected, analyzed and summarized to reach conclusions. The results of the research show that the house studied still maintains privacy even though the terrace of the house is used as an area for public access. This is intended as part of the homeowner's tolerance for neighbors who do not have access from the road to their residence